Pola Komunikasi Guru dengan Siswa Sekolah Menengah Sekolah Alam Bogor dalam Membangun Kepemimpinan - Dermawan, Nesya Hanifa; Putri, Yuliani Rachma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The lack of leadership development and moral values among students can result in deviant behaviors such as verbal and physical violence, and even substance abuse. This underscores the importance of character development and leadership among students. In this context, effective communication between teachers and students becomes crucial in addressing these challenges. This study aims to explore how teachers at SM Sekolah Alam Bogor communicate to instill leadership in their students. This research use qualitative method, using data collection techniques such as interviews, observations, and documentation. The findings suggest that various forms of communication patterns need to be applied to strengthen and complement the communication process between teachers and students. The implementation of leadership is found in various communication processes, whether through regular interactions, assigning tasks, classroom learning, or outdoor trips. Research also found that leadership qualities are present as evidenced by the impact shown by their senior students (SM 3).